Unravelling determinants of symptoms associated with environmental factors over time: Results from a representative sample - Tara Petzke; Ferenc Köteles; Renáta Szemerszky; Ralph C.A. Rippe; Michael Witthöft; Cédric Lemogne; Steven Nordin; Victor Pitron (International Journal of Hygiene and Environmental Health, 2026)

Analysis of second-generation epigenetic clocks reveals further associations between disproportionate biological ageing and hippocampal volume - Lidija Milicic; Michael Vacher; Vincent Doré; Pierrick Bourgeat; Rosita Shishegar; James D. Doecke; Paul Maruff; Christopher C. Rowe; Victor L. Villemagne; Michael Weiner; Paul Aisen; Ronald Petersen; et al. (GeroScience, 2026)

One or many environmental intolerance(s)? A cluster analysis over two representative samples - Tara M. Petzke; Ralph C.A. Rippe; Michael Witthöft; Renáta Szemerszky; Ferenc Köteles; Cédric Lemogne; Steven Nordin; Victor Pitron (International Journal of Hygiene and Environmental Health, 2026)

Vulnerability of marine megafauna to global at‐sea anthropogenic threats - Michelle VanCompernolle; Juliet Morris; Hannah J. Calich; Jorge P. Rodríguez; Sarah A. Marley; Jessica R. Pearce; Briana Abrahms; Katya Abrantes; André S. Afonso; Alex Aguilar; Andrews Agyekumhene; Tomonari Akamatsu; et al. (Conservation Biology, 2026)
Marine megafauna species are affected by a wide range of anthropogenic threats. To evaluate the risk of such threats, species’ vulnerability to each threat must first be determined. We build on the existing threats classification scheme and ranking system of the International Union for Conservation of Nature (IUCN) Red List of Threatened Species by assessing the vulnerability of 256 marine megafauna species to 23 at‐sea threats. The threats we considered included individual fishing gear types, climate‐change‐related subthreats not previously assessed, and threats associated with coastal impacts and maritime disturbances. Our ratings resulted in 70 species having high vulnerability ( v > 0.778 out of 1) to at least 1 threat, primarily drifting longlines, temperature extremes, or fixed gear. These 3 threats were also considered to have the most severe effects (i.e., steepest population declines). Overall, temperature extremes and plastics and other solid waste were rated as affecting the largest proportion of populations. Penguins, pinnipeds, and polar bears had the highest vulnerability to temperature extremes. Bony fishes had the highest vulnerability to drifting longlines and plastics and other solid waste; pelagic cetaceans to 4 maritime disturbance threats; elasmobranchs to 5 fishing threats; and flying birds to drifting longlines and 2 maritime disturbance threats. Sirenians and turtles had the highest vulnerability to at least one threat from all 4 categories. Despite not necessarily having severe effects for most taxonomic groups, temperature extremes were rated among the top threats for all taxa except bony fishes. The vulnerability scores we provide are an important first step in estimating the risk of threats to marine megafauna. Importantly, they help differentiate scope from severity, which is key to identifying threats that should be prioritized for mitigation.

The Toxicology Investigators Consortium 2024 Annual Report - Kim Aldy; Shao Li; Mari Costantini; Alyssa Falise; Rachel Culbreth; Paul M. Wax; Jeffery Brent; Michael Abesamis; Faiz Ahmed; Salman Ahsan; Peter Akpunonu; Adam Algren; et al. (Journal of Medical Toxicology, 2026)

Comparison between a chimeric anti-methamphetamine monoclonal antibody and humanized antibodies on pharmacological effects of methamphetamine - Michael Dale Berquist; Melinda Gunnell; Ralph Henry; William Brooks Gentry; Misty Ward Stevens (Psychopharmacology, 2025)

The giant barrel sponge Xestospongia muta takes up dissolved organic matter from benthic cyanobacterial mats - Lauren K. Olinger; Wendy K. Strangman; Steven E. McMurray; Ralph N. Mead; Joseph R. Pawlik (Organic Geochemistry, 2025)

Tracking data highlight the importance of human-induced mortality for large migratory birds at a flyway scale - Juan Serratosa; Steffen Oppel; Shay Rotics; Andrea Santangeli; Stuart H.M. Butchart; Luis S. Cano-Alonso; Jose Luis Tellería; Ryno Kemp; Aaron Nicholas; Aigars Kalvāns; Aitor Galarza; Aldina M.A. Franco; et al. (Biological Conservation, 2024)

The identification of airbursts in the past: Insights from the BIT-58 layer - Matthias van Ginneken; Ralph P. Harvey; Steven Goderis; Natalia Artemieva; Mark Boslough; Ryoga Maeda; Jérôme Gattacceca; Luigi Folco; Akira Yamaguchi; Corinne Sonzogni; Penelope Wozniakiewicz (Earth and Planetary Science Letters, 2024)

Observed and projected changes in snow accumulation and snowline in California’s snowy mountains - Tamara Shulgina; Alexander Gershunov; Benjamin J. Hatchett; Kristen Guirguis; Aneesh C. Subramanian; Steven A. Margulis; Yiwen Fang; Daniel R. Cayan; David W. Pierce; Michael Dettinger; Michael L. Anderson; F. Martin Ralph (Climate Dynamics, 2023)
The Sierra Nevada and Southern Cascades—California’s snowy mountains—are primary freshwater sources and natural reservoirs for the states of California and Nevada. These mountains receive precipitation overwhelmingly from wintertime storms including atmospheric rivers (ARs), much of it falling as snow at the higher elevations. Using a seven-decade record of daily observed temperature and precipitation as well as a snow reanalysis and downscaled climate projections, we documented historical and future changes in snow accumulation and snowlines. In four key subregions of California’s snowy mountains, we quantified the progressing contribution of ARs and non-AR storms to the evolving and projected snow accumulation and snowlines (elevation of the snow-to-rain transition), exploring their climatology, variability and trends. Historically, snow makes up roughly a third of the precipitation affecting California’s mountains. While ARs make up only a quarter of all precipitating days and, due to their relative warmth, produce snowlines higher than do other storms, they contribute over 40% of the total seasonal snow. Under projected unabated warming, snow accumulation would decline to less than half of historical by the late twenty-first century, with the greatest snow loss at mid elevations (from 1500 to 3300 m by the mountain sub-regions) during fall and spring. Central and Southern Sierra Nevada peaks above 3400 m might see occasionally extreme snow accumulations in January–February resulting entirely from wetter ARs. AR-related snowlines are projected to increase by more than 700 m, compared to about 500 m for other storms. We discuss likely impacts of the changing climate for water resources as well as for winter recreation.

Comprehensive analysis of epigenetic clocks reveals associations between disproportionate biological ageing and hippocampal volume - Lidija Milicic; Michael Vacher; Tenielle Porter; Vincent Doré; Samantha C. Burnham; Pierrick Bourgeat; Rosita Shishegar; James Doecke; Nicola J. Armstrong; Rick Tankard; Paul Maruff; Colin L. Masters; et al. (GeroScience, 2022)
The concept of age acceleration, the difference between biological age and chronological age, is of growing interest, particularly with respect to age-related disorders, such as Alzheimer’s Disease (AD). Whilst studies have reported associations with AD risk and related phenotypes, there remains a lack of consensus on these associations. Here we aimed to comprehensively investigate the relationship between five recognised measures of age acceleration, based on DNA methylation patterns (DNAm age), and cross-sectional and longitudinal cognition and AD-related neuroimaging phenotypes (volumetric MRI and Amyloid-β PET) in the Australian Imaging, Biomarkers and Lifestyle (AIBL) and the Alzheimer’s Disease Neuroimaging Initiative (ADNI). Significant associations were observed between age acceleration using the Hannum epigenetic clock and cross-sectional hippocampal volume in AIBL and replicated in ADNI. In AIBL, several other findings were observed cross-sectionally, including a significant association between hippocampal volume and the Hannum and Phenoage epigenetic clocks. Further, significant associations were also observed between hippocampal volume and the Zhang and Phenoage epigenetic clocks within Amyloid-β positive individuals. However, these were not validated within the ADNI cohort. No associations between age acceleration and other Alzheimer’s disease-related phenotypes, including measures of cognition or brain Amyloid-β burden, were observed, and there was no association with longitudinal change in any phenotype. This study presents a link between age acceleration, as determined using DNA methylation, and hippocampal volume that was statistically significant across two highly characterised cohorts. The results presented in this study contribute to a growing literature that supports the role of epigenetic modifications in ageing and AD-related phenotypes.

Unrestricted gene flow between two subspecies of translocated brushtail possums (Trichosurus vulpecula) in Aotearoa New Zealand - Nimeshika Pattabiraman; Mary Morgan-Richards; Ralph Powlesland; Steven A. Trewick (Biological Invasions, 2022)
Two lineages of brushtail possums ( Trichosurus vulpecula ) were historically introduced to Aotearoa New Zealand, and these two subspecies have different phenotypic forms. Despite over 100 years of potential interbreeding, they appear to retain morphological differences, which may indicate reproductive isolation. We examined this using population samples from a confined landscape and scored each specimen for phenotype using a number of fur colour traits. This resulted in a bimodal trait distribution expected for segregated grey and black lineages. We also sought evidence for genetic partitioning based on spatial and temporal effects. Genetic structure and rates of genetic mixing were determined using seven neutral, species-specific nuclear microsatellite markers and mitochondrial DNA control region sequence. Genotype analyses indicated high levels of variation and mtDNA sequences formed two major haplogroups. Pairwise tests for population differentiation of these markers found no evidence of subdivision, indicating that these brushtail possums behave as a single randomly mating unit. Despite maintenance of two main colour phenotypes with relatively few intermediates, previous inference of assortative mating and anecdotes of distinct races, our data indicate that New Zealand brushtail possums can freely interbreed, and that in some locations they have formed completely mixed populations where neutral genetic markers are unrelated to phenotype. This has implications for effective pest management towards eradication.

Evaluating the potential of full‐waveform lidar for mapping pan‐tropical tree species richness - Suzanne M. Marselis; Katharine Abernethy; Alfonso Alonso; John Armston; Timothy R. Baker; Jean‐Francois Bastin; Jan Bogaert; Doreen S. Boyd; Pascal Boeckx; David F. R. P. Burslem; Robin Chazdon; David B. Clark; et al. (Global Ecology and Biogeography, 2020)
Aim Mapping tree species richness across the tropics is of great interest for effective conservation and biodiversity management. In this study, we evaluated the potential of full‐waveform lidar data for mapping tree species richness across the tropics by relating measurements of vertical canopy structure, as a proxy for the occupation of vertical niche space, to tree species richness. Location Tropics. Time period Present. Major taxa studied Trees. Methods First, we evaluated the characteristics of vertical canopy structure across 15 study sites using (simulated) large‐footprint full‐waveform lidar data (22 m diameter) and related these findings to in‐situ tree species information. Then, we developed structure–richness models at the local (within 25–50 ha plots), regional (biogeographical regions) and pan‐tropical scale at three spatial resolutions (1.0, 0.25 and 0.0625 ha) using Poisson regression. Results The results showed a weak structure–richness relationship at the local scale. At the regional scale (within a biogeographical region) a stronger relationship between canopy structure and tree species richness across different tropical forest types was found, for example across Central Africa and in South America [ R 2 ranging from .44–.56, root mean squared difference as a percentage of the mean (RMSD%) ranging between 23–61%]. Modelling the relationship pan‐tropically, across four continents, 39% of the variation in tree species richness could be explained with canopy structure alone ( R 2 = .39 and RMSD% = 43%, 0.25‐ha resolution). Main conclusions Our results may serve as a basis for the future development of a set of structure–richness models to map high resolution tree species richness using vertical canopy structure information from the Global Ecosystem Dynamics Investigation (GEDI). The value of this effort would be enhanced by access to a larger set of field reference data for all tropical regions. Future research could also support the use of GEDI data in frameworks using environmental and spectral information for modelling tree species richness across the tropics.

A model-based assay design to reproduce in vivo patterns of acute drug-induced toxicity - Lars Kuepfer; Olivia Clayton; Christoph Thiel; Henrik Cordes; Ramona Nudischer; Lars M. Blank; Vanessa Baier; Stephane Heymans; Florian Caiment; Adrian Roth; David A. Fluri; Jens M. Kelm; et al. (Archives of Toxicology, 2018)

Incidental retrieval of prior emotion mimicry - Ralph Pawling; Alexander J. Kirkham; Amy E. Hayes; Steven P. Tipper (Experimental Brain Research, 2017)

Naturally p-Hydroxybenzoylated Lignins in Palms - Fachuang Lu; Steven D. Karlen; Matt Regner; Hoon Kim; Sally A. Ralph; Run-Cang Sun; Ken-ichi Kuroda; Mary Ann Augustin; Raymond Mawson; Henry Sabarez; Tanoj Singh; Gerardo Jimenez-Monteon; et al. (BioEnergy Research, 2015)

Can macroalgae contribute to blue carbon? An A ustralian perspective - Ross Hill; Alecia Bellgrove; Peter I. Macreadie; Katherina Petrou; John Beardall; Andy Steven; Peter J. Ralph (Limnology and Oceanography, 2015)
Macroalgal communities in Australia and around the world store vast quantities of carbon in their living biomass, but their prevalence of growing on hard substrata means that they have limited capacity to act as long‐term carbon sinks. Unlike other coastal blue carbon habitats such as seagrasses, saltmarshes and mangroves, they do not develop their own organic‐rich sediments, but may instead act as a rich carbon source and make significant contributions in the form of detritus to sedimentary habitats by acting as a “carbon donor” to “receiver sites” where organic material accumulates. The potential for storage of this donated carbon however, is dependent on the decay rate during transport and the burial efficiency at receiver sites. To better understand the potential contribution of macroalgal communities to coastal blue carbon budgets, a comprehensive literature search was conducted using key words, including carbon sequestration, macroalgal distribution, abundance and productivity to provide an estimation of the total amount of carbon stored in temperate Australian macroalgae. Our most conservative calculations estimate 109.9 Tg C is stored in living macroalgal biomass of temperate Australia, using a coastal area covering 249,697 km 2 . Estimates derived for tropical and subtropical regions contributed an additional 23.2 Tg C. By extending the search to include global studies we provide a broader context and rationale for the study, contributing to the global aspects of the review. In addition, we discuss the potential role of calcium carbonate‐containing macroalgae, consider the dynamic nature of macroalgal populations in the context of climate change, and identify the knowledge gaps that once addressed will enable robust quantification of macroalgae in marine biogeochemical cycling of carbon. We conclude that macroalgal communities have the potential to make ecologically meaningful contributions toward global blue carbon sequestration, as donors, but given that the fate of detached macroalgal biomass remains unclear, further research is needed to quantify this contribution.

No evidence of interaction between known lipid-associated genetic variants and smoking in the multi-ethnic PAGE population - Logan Dumitrescu; Cara L. Carty; Nora Franceschini; Lucia A. Hindorff; Shelley A. Cole; Petra Bůžková; Fredrick R. Schumacher; Charles B. Eaton; Robert J. Goodloe; David J. Duggan; Jeff Haessler; Barbara Cochran; et al. (Human Genetics, 2013)

A dynamic model of the cellular carbon to chlorophyll ratio applied to a batch culture and a continental shelf ecosystem - Mark E. Baird; Peter J. Ralph; Farhan Rizwi; Karen Wild-Allen; Andrew D. L. Steven (Limnology and Oceanography, 2013)
A novel parameterization of the dynamical relationship between cellular carbon (C) and chlorophyll (Chl) is developed using a Chl synthesis term that includes the physiological status of the cell and the effect of packaging of pigments within cells. The geometric derivation highlights the non‐linear relationship between Chl content and absorption due to the package effect. When parameterized for a generic 3 µm radius phytoplankton cell, the model reproduces the magnitude and daily variations of C : Chl and C : nitrogen ratios of the diatom Skeletonema costatum in published laboratory experiments. The parameterization is then applied in a three‐dimensional biogeochemical model containing three phytoplankton classes in the coastal waters off southeast Tasmania, Australia, which demonstrates the behavior of the dynamic Chl parameterization over a range of light‐ and nutrient‐limiting environments for phytoplankton of different sizes and growth rates. The model produces C : Chl ratios of ∼ 12–20 (weight : weight) and ∼ 60–80 for phytoplankton communities dominated by fast‐growing small and fast‐growing large cells, respectively, close to the ratios of 17 and 76 observed at two sampling stations during periods with diatom‐ and flagellate‐dominated communities. Throughout the simulation, community C : Chl ratios generally vary between 12 and 200, which is similar to the range observed globally. In the new parameterization, C : Chl ratios are most influenced by the package effect for light‐limited, slow‐growing large microalgae, with physiological processes becoming important for smaller, nutrient‐limited, fast‐growing microalgae.

The interaction between land use and catchment physiognomy: understanding avifaunal patterns of the Murray–Darling Basin, Australia - Steven Camilleri; James R. Thomson; Ralph Mac Nally (Journal of Biogeography, 2010)
Aim We assessed whether different patterns of land use within similar physiognomic catchments (= watersheds) produced discernible effects on avian assemblages and, if so, whether such effects were related to particular land‐use activities (e.g. extensive cropping). Location Murray–Darling Basin in south‐eastern Australia. Methods We used a recently (2007) published physiognomic classification of catchments based on different stream orders as our template. We used a subset of data from the second Birds Australia atlas to calculate reporting rates for each species in each subcatchment. We linked these two sets of data with proportions of major land uses within catchments to identify whether differences in proportions of land uses altered the expected avifauna for catchments of the same nominal physiognomic class. Results A significant proportion of the variation in bird reporting rates was explained by the physiognomic classification. Additional explanatory power resulted from including an interaction matrix of land‐use covariates. Livestock grazing was a major explanatory variable in classes characterized by more mountainous catchments. Cropping affected avifaunas consistently by producing a more uniform assemblage. Main conclusions The physiognomic template was an important determinant of avifaunal composition, but its interaction with land‐use variation within physiognomic classes doubled the amount of variance explained. Within a physiognomic class, if one identifies the ‘ideal’ avifaunal composition for that class one can identify land‐use mixes that are most likely to be beneficial for the avifaunas of that class and recommend directions for large‐scale management objectives vis‐à‐vis mixtures of land‐use types.

Tidal flows in Te Aumiti (French Pass), South Island, New Zealand - Craig Stevens; Philip Sutton; Murray Smith; Ralph Dickson (New Zealand Journal of Marine and Freshwater Research, 2008)
Observations of tidal flows in Te Aumiti (French Pass), the fastest such flows in New Zealand, were conducted in 2006 using a vessel‐mounted acoustic Doppler current profiler (ADCP), pressure sensors, a current meter mooring, drifters, and microwave radar. The suite of measurements revealed spring tide currents exceeding 4 m s ‐1 , but only in the throat of the pass. The pressure sensors either side of the pass indicated a phase‐shift in the tide of 26 min. Drifters illustrated eddying motion, with the deep scour hole on the NE side of the narrows forming a focal point on both phases of the tide. Notably, the drifters also provided evidence of an upstream eddy in the same location during southwestward flows. The ADCP recorded vertical flows of up to 0.6 m s ‐1 . The flow was subcritical as defined by external and internal Froude numbers, and scaling analysis suggests that the driving pressure gradient was balanced by the acceleration.

CYP82E4-mediated nicotine to nornicotine conversion in tobacco is regulated by a senescence-specific signaling pathway - Manohar Chakrabarti; Steven W. Bowen; Nicholas P. Coleman; Karen M. Meekins; Ralph E. Dewey; Balazs Siminszky (Plant Molecular Biology, 2008)

Functional identification and differential expression of 1-deoxy-d-xylulose 5-phosphate synthase in induced terpenoid resin formation of Norway spruce (Picea abies) - Michael A. Phillips; Michael H. Walter; Steven G. Ralph; Paulina Dabrowska; Katrin Luck; Eva Maria Urós; Wilhelm Boland; Dieter Strack; Manuel Rodríguez-Concepción; Jörg Bohlmann; Jonathan Gershenzon (Plant Molecular Biology, 2007)

Characterization of EST-SSRs in loblolly pine and spruce - Yanik Bérubé; Jun Zhuang; Dainis Rungis; Steven Ralph; Jörg Bohlmann; Kermit Ritland (Tree Genetics & Genomes, 2007)

Evaluation of Three-dimensional Image Registration Methodologies for In Vivo Micro-computed Tomography - Steven K. Boyd; Stephan Moser; Michael Kuhn; Robert J. Klinck; Peter L. Krauze; Ralph Müller; Jürg A. Gasser (Annals of Biomedical Engineering, 2006)

Ethylene in induced conifer defense: cDNA cloning, protein expression, and cellular and subcellular localization of 1-aminocyclopropane-1-carboxylate oxidase in resin duct and phenolic parenchyma cells - J. W. Hudgins; Steven G. Ralph; Vincent R. Franceschi; Jörg Bohlmann (Planta, 2006)

Genomics of hybrid poplar ( Populus trichocarpa × deltoides ) interacting with forest tent caterpillars ( Malacosoma disstria ): normalized and full‐length cDNA libraries, expressed sequence tags, and a cDNA microarray for the study of insect‐induced defences in poplar - STEVEN RALPH; CLAIRE ODDY; DAWN COOPER; HESTHER YUEH; SHARON JANCSIK; NATALIA KOLOSOVA; RYAN N. PHILIPPE; DANA AESCHLIMAN; RICK WHITE; DEZENE HUBER; CAROL E. RITLAND; FRANÇOIS BENOIT; et al. (Molecular Ecology, 2006)
As part of a genomics strategy to characterize inducible defences against insect herbivory in poplar, we developed a comprehensive suite of functional genomics resources including cDNA libraries, expressed sequence tags (ESTs) and a cDNA microarray platform. These resources are designed to complement the existing poplar genome sequence and poplar ( Populus spp.) ESTs by focusing on herbivore‐ and elicitor‐treated tissues and incorporating normalization methods to capture rare transcripts. From a set of 15 standard, normalized or full‐length cDNA libraries, we generated 139 007 3′‐ or 5′‐end sequenced ESTs, representing more than one‐third of the c. 385 000 publicly available Populus ESTs. Clustering and assembly of 107 519 3′‐end ESTs resulted in 14 451 contigs and 20 560 singletons, altogether representing 35 011 putative unique transcripts, or potentially more than three‐quarters of the predicted c. 45 000 genes in the poplar genome. Using this EST resource, we developed a cDNA microarray containing 15 496 unique genes, which was utilized to monitor gene expression in poplar leaves in response to herbivory by forest tent caterpillars ( Malacosoma disstria ). After 24 h of feeding, 1191 genes were classified as up‐regulated, compared to only 537 down‐regulated. Functional classification of this induced gene set revealed genes with roles in plant defence (e.g. endochitinases, Kunitz protease inhibitors), octadecanoid and ethylene signalling (e.g. lipoxygenase, allene oxide synthase, 1‐aminocyclopropane‐1‐carboxylate oxidase), transport (e.g. ABC proteins, calreticulin), secondary metabolism [e.g. polyphenol oxidase, isoflavone reductase, (–)‐germacrene D synthase] and transcriptional regulation [e.g. leucine‐rich repeat transmembrane kinase, several transcription factor classes (zinc finger C3H type, AP2/EREBP, WRKY, bHLH)]. This study provides the first genome‐scale approach to characterize insect‐induced defences in a woody perennial providing a solid platform for functional investigation of plant–insect interactions in poplar.

Spatial and temporal variation in tissue halide levels of Salicornia virginica - Yvette Ralph; Steven L. Manley (Wetlands, 2006)

Dirigent Proteins in Conifer Defense: Gene Discovery, Phylogeny, and Differential Wound- and Insect-induced Expression of a Family of DIR and DIR-like Genes in Spruce (Picea spp.) - Steven Ralph; Ji-Young Park; Jörg Bohlmann; Shawn D. Mansfield (Plant Molecular Biology, 2006)

Methadone and nicotine self-administration in humans: a behavioral economic analysis - Ralph Spiga; Margaret P. Martinetti; Richard A. Meisch; Katherine Cowan; Steven Hursh (Psychopharmacology, 2005)

GENOMIC HARDWIRING AND PHENOTYPIC PLASTICITY OF TERPENOID-BASED DEFENSES IN CONIFERS - DEZENE P. W. HUBER; STEVEN RALPH; JRG BOHLMANN (Journal of Chemical Ecology, 2004)

Robust simple sequence repeat markers for spruce (Picea spp.) from expressed sequence tags - Dainis Rungis; Yanik Brub; Jun Zhang; Steven Ralph; Carol E. Ritland; Brian E. Ellis; Carl Douglas; Jrg Bohlmann; Kermit Ritland (Theoretical and Applied Genetics, 2004)